Diversification Strategies On Corporate Performance: An Empirical Study On Malaysia Firms - Yaghoubi, Mona (2009)
This study discusses the theoretical issues on diversification, corporate performance and the relationship between these two. It studies 91 listed firms in the Main Board of Bursa Malaysia (Trading/Services ranking) for determining the diversification-performance relationship. Generally, the main objective of this research is to find out if different levels of diversification lead to different levels of corporate performance or not. Besides, the study looks for the effect of economic situation on the diversification-performance relationship. The time period of the study was chosen from 1997 to 2002, including the 1997-1998 East-Asian financial crisis.